Site Damage Tests of Geotextiles Used for Layer Separation in Road Construction - Audrius Vaitkus; Alfredas Laurinavičius; Donatas Čygas (The Baltic Journal of Road and Bridge Engineering)
In recent decades Lithuania has witnessed an increase in road construction and reconstruction works involving the use of geosynthetics, which is usually concerned with special functions. One of them is separation of layers of aggregate by geotextile in the structure of road pavement. To successfully implement the separation, there are several crucial factors to be taken into consideration: the integrity, durability of the material and damages identified during installation. In Lithuania the geosynthetics is selected on the basis of eight-year-old interim guidelines and recommendations of suppliers. The paper deals with the systems of selecting geosynthetics in Lithuania and other countries. Then the results of experimental research are assessed. The present research has selected 5 types of geosynthetics of some manufacturers. The geotextiles were installed between different layers of road pavement structure. The analysis focuses on geotextile damages emerging during installation and their impact on performing the function of separation.